2018
DOI: 10.1074/jbc.ra118.003373
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor NKX2-3 mediates p21 expression and ectodysplasin-A signaling in the enamel knot for cusp formation in tooth development

Abstract: Tooth morphogenesis is initiated by reciprocal interactions between the ectoderm and neural crest-derived mesenchyme. During tooth development, tooth cusps are regulated by precise control of proliferation of cell clusters, termed enamel knots, that are present among dental epithelial cells. The interaction of ectodysplasin-A (EDA) with its receptor, EDAR, plays a critical role in cusp formation by these enamel knots, and mutations of these genes is a cause of ectodermal dysplasia. It has also been reported th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 51 publications
5
25
0
Order By: Relevance
“…From this situation, it is possible that the molars did not have hair structures because they did not have sufficient time to grow. Previously, we showed that the basement membrane component nephronectin and NKX2-3 inhibit Sox2 expression in the dental epithelium ( Arai et al., 2017 ; Han et al., 2018 ). However, nephronectin was downregulated in differentiated ameloblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From this situation, it is possible that the molars did not have hair structures because they did not have sufficient time to grow. Previously, we showed that the basement membrane component nephronectin and NKX2-3 inhibit Sox2 expression in the dental epithelium ( Arai et al., 2017 ; Han et al., 2018 ). However, nephronectin was downregulated in differentiated ameloblasts.…”
Section: Discussionmentioning
confidence: 99%
“…The process of ectodermal organ morphogenesis is highly conserved and largely regulated by the same genes, hence various developmental defects are often observed concordantly in several ectodermal organs. For example, patients with syndromes such as incontinentia pigmenti ( Smahi et al., 2000 ), Langer-Giedion ( Momeni et al., 2000 ), Ellis-van Creveld ( Ruiz-Perez et al., 2003 ), tricho-dento-osseous ( Price et al., 1998 ), anhidrotic ectodermal dysplasia ( Srivastava et al., 1996 ; van der Hout et al., 2008 ), hidrotic ectodermal dysplasia ( Han et al., 2018 ; Lamartine et al., 2000 ), Hallermann-Streiff ( Pizzuti et al., 2004 ), and Menkes ( Tumer et al., 2003 ) have dysplasia in both teeth and hair.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we have reported the biological roles of previously uncharacterized genes in tooth development (17)(18)(19). Furthermore, the functions that are characteristically expressed in tooth and affect tooth differentiation have been elucidated (20)(21)(22)(23)(24). In the present study, we focused on Gpr115 as a candidate key factor for tooth development.…”
mentioning
confidence: 94%
“…For a better understanding of the molecular mechanism during tooth development, we had previously identified several genes preferentially expressed in ameloblast lineage and had analyzed their roles in tooth development ( Saito et al, 2015 ; Liu J. et al, 2016 ; Miyazaki et al, 2016 ; Nakamura et al, 2016 ; Arai et al, 2017 ; Han et al, 2018 ; Nakamura et al, 2020 ). We had also identified novel genes from tooth germ complementary DNA library, namely Ameloblastin ( Ambn ), Epiprofin ( Epfn ), and AmeloD ( Dhamija et al, 1999 ; Nakamura et al, 2004 ; He et al, 2019 ), and each of these knockout mice models showed severe enamel hypoplasia ( Fukumoto et al, 2004 ; Nakamura et al, 2008 , 2017 ; Aurrekoetxea et al, 2016 ; Chiba et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%